TRANSITIONING TO A GREEN ECONOMY: OPPORTUNITIES AND CHALLENGES FOR DEVELOPING COUNTRIES - Khodjamuratova Gulbahor Yuldashevna (Modern American Journals, 2025)
The transition to a green economy presents both opportunities and challenges for developing countries. This paper explores how sustainable economic growth can be achieved through the adoption of renewable energy, eco-friendly production, and green employment initiatives. It highlights the importance of policy reforms, technology transfer, and international cooperation in promoting environmentally responsible development. While the green transition offers significant social and economic benefits, such as poverty reduction and job creation, it also poses financial and infrastructural challenges that must be addressed to ensure inclusive and equitable progress.
Keywords: Green economy, sustainable development, renewable energy, developing countries, environmental policy, green jobs, climate change